A short geriatric assessment tool for the older person with cancer in India-Development and psychometric validation. Issue 2 (March 2019) - Banerjee, Joyita; Satapathy, Sujata; Upadhyay, Ashish Dutt; Dwivedi, Sada Nand; Chatterjee, Prasun; Kumar, Lalit; Rath, Goura Kishor; Dey, Aparajit Ballav
Abstract: Introduction: With rise in incidence and prevalence of cancers in the ageing population, the need for an age sensitive comprehensive assessment measure has been felt. Comprehensive Geriatric Assessment (CGA) is often difficult to implement due to time and logistic constraints. A brief assessment tool encompassing the specific domains of the CGA would be a better way to assess older adults with cancer. These tools exist but have not necessarily been culturally adapted. The main aim of the study was to develop a culturally relevant short geriatric assessment tool and explore its psychometric properties. Methodology: An initial item pool was formed after review of the literature and study of the existing scales. This draft tool was then pre and pilot tested to finalize the items and check the feasibility of application. The final tool was validated by exploratory factor analysis on a sample of 100 older patients with cancer. Results: After pre and pilot study on fifteen and thirty older patients with cancer respectively, this tool consisting of a total of 38 items spread over eight domains was developed and validated on a sample of 100 subjects. Due to co-linearity, three items were deleted after exploratory factor analysis, bringing the final item number to35. The Cronbach's alpha was 0.93 and the intra-class correlation co-efficient (ICC) was 0.94. Thus, the final tool had 13 questions with sub-parts (35 items in total). The time taken to administer the tool was around 25 min. Conclusion: The tool developed is valid and reliable and can be used for the initial assessment and further care planning of older Indian patients with cancer.